2020
DOI: 10.1111/sode.12438
|View full text |Cite
|
Sign up to set email alerts
|

RWAc and SDOc: The measurement of right‐wing authoritarianism and social dominance orientation in childhood

Abstract: Right-wing authoritarianism (RWA) and social dominance orientation (SDO) predict prejudice and discrimination in adults. To create analogous scales for children, we carried out four studies. First, we gave 112 adults from New Zealand (Study 1) and 146 adults from Turkey (Study 2) novel child-appropriate measures of RWA and SDO, along with the standard adult measures. The two RWA measures correlated more highly with each other than with the SDO measures, and the two SDO measures correlated more highly with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…TIV is an important variable to account for particularly in ROI-based volumetric measures because such subtle differences in regional brain volume may be confounded by individual differences in overall brain size [ 84 ]. We are also controlling for age not only because TIV varies as a function of age [ 85 ], but also because both RWA and SDO have been shown to decrease with age [ 1 , 42 ]. Accounting for age is also necessitated in this study because the analysis will include participants from two different age groups, a young adult sample and a middle-aged adult sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TIV is an important variable to account for particularly in ROI-based volumetric measures because such subtle differences in regional brain volume may be confounded by individual differences in overall brain size [ 84 ]. We are also controlling for age not only because TIV varies as a function of age [ 85 ], but also because both RWA and SDO have been shown to decrease with age [ 1 , 42 ]. Accounting for age is also necessitated in this study because the analysis will include participants from two different age groups, a young adult sample and a middle-aged adult sample.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, people vary in their levels of RWA and SDO. These differences tend to decrease with age but show reasonable consistency in adult samples [42]. Despite being measured as separate scales in most research, some have raised the possibility that the correlation between RWA and SDO might denote that they can be subsumed to a uni-dimensional spectrum [43,44]; for opposing views, see [30,45].…”
Section: Introductionmentioning
confidence: 99%
“…Three other findings suggest the presence of early individual differences in proto‐political expressions of social dominance. First, Ruffman and colleagues (2020) adapted an adult self‐report measure of SDO for use with children and found that SDO scores among 9‐ to 12‐year‐old children correlated with their mothers' levels of SDO (and authoritarianism). We note, however, that this self‐report measure had low reliability among the 6‐ to 8‐year‐olds in their sample and was thus not included in analyses.…”
Section: What Is Political Ideology?mentioning
confidence: 99%
“…Another means of testing whether the individual differences in young children's proto‐political attitudes are early expressions of ideological orientation is to test whether these individual differences predict the outcomes that authoritarianism has been shown to predict among adults. Following this logic, Ruffman and colleagues (2020) tested the validity of a child‐friendly adaptation of an adult authoritarianism self‐report measure by exploring this adapted measure's associations with outcomes favored by authoritarian adults. Indeed, 6‐ to 12‐year‐old children's responses on this new scale were associated with a preference to play with an ingroup over an outgroup member and with a conventional over a nonconventional individual (based on physical appearance).…”
Section: What Is Political Ideology?mentioning
confidence: 99%
“…An emerging field of research has suggested that differences related to political orientation can be detected very early in life [38,39] and parents' ideology, through both genes and socialization, may affect their children's ideology precursors [40][41][42][43][44]. In other words, children of conservative parents seem to differ from children of liberal parents, displaying a set of characteristics predisposing either to conservatism or to liberalism.…”
Section: The Antecedents Of Inequality Aversionmentioning
confidence: 99%